Change in yield and botanical composition with different altitudes of natural rangeland: Turkey, Siirt province Central district Doluharman village rangeland - Sefa Süleyman Taşdelen; Mehmet Arif Özyazıcı (Turkish Journal of Forestry, 2022)
In this study, it was aimed to determine the effect of altitude differences on vegetation composition and productivity in rangeland under semi-arid climate conditions. The research was carried out in 3 different altitudes (620, 770, and 920 m) of Doluharman village natural rangeland, in the Central district of Siirt province, located in the Southeastern Anatolia Region of Turkey in 2021. Vegetation studies were carried out in May and the modified wheeled loop (ring) method was used in the measurements. The health classification of rangelands with different altitudes was determined by evaluating fresh forage and hay yields, the proportions of grasses, legumes, and other family plants in the botanical composition by weight, and the soil coverage ratio of the vegetation in the examined rangeland sections. Families, life spans, and impact degrees (decreaser, increaser, and invasive species) of plant species encountered in the vegetation study were determined. According to the results of the research, it was determined that all of the parameters examined depending on the altitudes varied significantly. Accordingly, fresh forage and hay yields obtained from the rangeland were increased in parallel with the increase in altitude, and yields were determined as average 404.92 and 141.97 kg/da, respectively. It was found that the proportion of grasses in the botanical composition by weight was high at all altitudes. In the botanical composition, the average rate of grasses was 73.63%, legumes were 11.90% and other family plants were 14.47%. In the study, the rate of soil coverage by plants increased depending on the increase in altitude. The average soil coverage rate of the rangeland was determined as 71.50%. Accordingly, the health class of the examined rangeland was evaluated as “healthy”. However, in vegetation surveys, it was determined that invasive species were in the majority in all altitudes parts of the rangeland. According to these results, it was concluded that it would be appropriate to graze the rangeland in accordance with the principles of rangeland management and that there is a need for improvement work in the said rangeland area.